An implementation of e-learning application in a Macedonian higher-education institution : a case study of State University of Tetova - Kartiwi, Mira; Esati, Elfat (IIUM Press, 2011)
The purpose of the paper you are holding will give a skeleton description and structure of the Course Repository of State University of Tetova located in Macedonia. It will try to ease the sharing of course materials, the communication between the lecturers and students and also for an effective way of teaching. With the implementation of the system the students will be able to access files that have been uploaded by the lecturers, view announcement, submit assignments and many sub functions. The students will be aware for any changes made to the course they are registered by receiving e-mails. The main users of the system as mentioned above will be the students and lecturers. The lecturers will log in to the system using their own IDs provided by the university at the time they have taken place of work in the university, the students would use their ID's that they have at the time of registration at the university. The system will also keep information about the students such as their personal information, academic matters, such as study plan and so on.